Faaliyatu Toriqoti al-Hifri Fii Ta'liimi al-Mufradat - Rofat Hizmatul Himmah; Nivela Ristin (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2021)
The purpose of this research to know how the drill method is implemented and how effective the drill method is in learning Arabic vocabulary. This research is a quasi-experimental research. This research was conducted at MTs Al-Amiriyyah. The population in this study were students of class VIII MTs Al-Amiriyyah, amounting to 140 students. The samples taken were the control class as many as 34 students and the experimental class as many as 35 students. The experimental class was treated using the drill method in learning Arabic vocabulary, while the control class only used conventional methods. The design used in this study is the Pre-Test Post-Test Control Group Design. The research instrument was in the form of a learning outcome test. To test the hypothesis using the paired sample t-test. Data analysis was done descriptively-quantitatively. The results of this study indicate that: (1) in the control class the average value of the pretest is 59.94 while the posttest average value of 77.17 is still lower than the experimental class, (2) in the experimental class the average value of the pretest is 77.17. 59.54 while the posttest average value of 88.17 is higher than the control class, (3) the average posttest value of the experimental class > control class is 88.17 > 77.17 which means that the experimental class learning outcomes are higher than the control class. control class, in the paired t-test, the results obtained are sig.2 tailed of 0.000 <0.05. The use of the drill method in learning Arabic vocabulary is more effective.